Korelasi Kupu-Kupu dengan Tumbuhan Berbungga pada Pandemi Covid-19 di Taman Margasatwa Ragunan Jakarta Selatan - Hasni Ruslan; Yohanna Puspita Anggraeni; Abdau Satiyo (Seminar Nasional Lahan Suboptimal, 2021)
Ruslan H, Anggraeni YP, Satiyo A. 2021. Butterfly and flowering plant correlation during Covid-19 pandemic in Ragunan Wildlife Park. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-9 Tahun 2021, Palembang 20 Oktober 2021. pp. 194-201.  Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI). Ragunan Wildlife Park is a conservation area, one of the existing fauna, is a butterfly. Butterflies are known to act as indicators of habitat change. This study aims to determine the correlation between butterflies and flowering plants. This study uses a descriptive method by determining the plot by purposive sampling, using insect nets and cameras. The study was conducted for three days, in three locations (location I at the west door. Location II at the east door, and location III at the south door). The research was conducted at 09.00-12.00. In this study, a total of 159 individual butterflies from 5 families were found, namely: Papilionidae, Pieridae, Nymphalidae, Lycaenidae, and Hesperiidae, and 24 species. The Nymphalidae family was found with a high number of species, while the Lycaenidae family was found with a high number of individuals. There were similarities in the composition of butterflies in locations I-II, and I-III. At locations II-III, there is no similarity in the composition of butterflies. The butterfly diversity index at locations 1 and II was moderate, with. evenness index is high. At location III the diversity index is low, with the evenness index being moderate. At locations I, and II, the light intensity was higher than at locations III. Butterflies were found with high importance index in Zizina otis, Ypthima philomela, Appias olferna, and Leptosia nina species. The abiotic data found at the three locations showed the optimum range for butterfly life. Based on the Pearson correlation, there is a strong relationship between flowering plants and the number of individual butterflies. A strong relationship is seen in the Zizina otis butterfly with Asystasia gangetica and Commelina virginica plants.